POENA CULLEI. KARA CZY RYTUAŁ? - Jońca, Maciej (Zeszyty Prawnicze, 2017)
Poena cullei. Penalty or Ritual? Summary Poena cullei appears to have been one of the most severe and cruel penalties in Roman criminal law. A convict was sewn up in a leather sack and drowned either in the river or in the sea. This sort of punishm ent was mainly inflicted on kin-murderers, which finds its reflection in numerous ancient sources which describe it as poena parricidi. Kin-murderers are claimed to have been liable to such retribution since the punic wars, and this sanction remained effective all throughout the period of Roman state. The sack penalty was more an act of a purification than a penal sanction in its legal meaning. A kin-m urder was perceived by the Roman society as an appalling act bringing pollution not only upon its perpetrator but also the whole community. In order to restore the previous state of order, the society had to get rid of a criminal in the course of a special ritual. At first a convict was flogged with red rodds. Then he had a lupine mask and clogs put on, to be finally sewn up in a sack with four animals - a dog, a monkey, a cock and a viper and afterwards drowned. According to the Romans, a dog, a cock and a viper were horrible animals. They believed a m urderer would undergo a transformation from a hum an being to a blood-thirsty beast. Surprisingly, the three mentioned above creatures had chtonic character and each of them was supposed to play a crucial part in the underworld. The worst consequences ofpoena cullei were to appear after the death of a criminal. During this gloomy ceremony abolitio imaginis was imposed and a m urderer was deprived of the right to a decent burial. This sort of procedure was applied throughout centuries and even in Christian Times did not lose its religious-ritual nature.